2007
DOI: 10.1021/jf063775l
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and α-Farnesene Metabolism in Green and Red Skin of Three Apple Cultivars in Response to 1-Methylcyclopropene (1-MCP) Treatment

Abstract: Relationships among alpha-farnesene synthesis and oxidation, ethylene production and perception, antioxidative enzyme activities, and superficial scald development in fruit of three commercial apple cultivars were investigated at the biochemical and gene transcriptional levels. Scald-susceptible Cortland and Law Rome and scald-resistant Idared apples were untreated or treated with the ethylene action inhibitor 1-methylcyclopropene (1-MCP) and stored for up to 25 weeks at 0.5 degrees C. Separate blushed (red) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 56 publications
8
29
0
8
Order By: Relevance
“…However, we observed significant differences in ethylene production among the five cultivars as well as differential response of these cultivars to the 1-MCP treatment in the two storage durations. Our results are in agreement with earlier observations made by Tsantili et al [34]. Additionally, Watkins et al [19] showed different sensitivity to 1-MCP among four apple cultivars, resulting in different degree of inhibition of ethylene production.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, we observed significant differences in ethylene production among the five cultivars as well as differential response of these cultivars to the 1-MCP treatment in the two storage durations. Our results are in agreement with earlier observations made by Tsantili et al [34]. Additionally, Watkins et al [19] showed different sensitivity to 1-MCP among four apple cultivars, resulting in different degree of inhibition of ethylene production.…”
Section: Resultssupporting
confidence: 94%
“…Tsantili et al [34] reported different levels of ethylene synthesis between "Cortland," "Law Rome," and "Idared" apples during 25 weeks of storage at 0.5 ∘ C. The 1-MCP effect on ethylene production also slightly differed among cultivars. Although 1-MCP reduced ethylene production in many apple cultivars, the rate of synthesis started to increase after 5 weeks of storage in "Cortland" and "Law Rome" apples, while it stayed relatively constant in "Idared" fruits after 25 weeks of storage [34]. In the present study, 1-MCP treatment reduced ethylene production in all five cultivars.…”
Section: Resultsmentioning
confidence: 97%
“…This agrees with what has been reported by several studies Watkins et al, 2000;DeEll et al, 2002;Shaham et al, 2003;Zanella, 2003;DeLong et al, 2004) and reaffirms that the control is a function of an inhibition of ethylene that regulates lower AF production Watkins et al, 2000;Golding et al, 2001;Shaham Arquiza et al, 2005;Tsantili et al, 2007) and its consequent oxidation of TC, in particular TC 281.…”
Section: Chemical Compounds and The Incidence Of Superficial Scaldsupporting
confidence: 90%
“…Todavia, menores benefícios do 1-MCP são observados em maçãs colhidas em estádio avançado de maturação (ARGENTA et al, 2005) ou tratadas depois de decorrido certo tempo de armazenamento refrigerado (ARGENTA et al, 2005;NOCK, 2005;JUNG;WATKINS, 2008). A menor eficiência do 1-MCP nestas condições é resultado do maior acúmulo de transcritos dos genes das rotas de biossíntese de etileno e de a-farneseno (PECHOUS et al, 2005;TSANTILI et al, 2007).…”
Section: Introductionunclassified